Economic analysis of turmeric cultivation: evidence from Khagrachari district - Begum, MEA; Miah, MA Monayem; Rashid, MA; Islam, MT; Hossain, MI (Bangladesh Journal of Agricultural Research, 2019)
Turmeric is a good source of income for hilly people of Bangladesh. The study estimated the profitability and technical efficiency of turmeric cultivation in Khagrachhari district. In total 150 turmeric farms located in Khagrachari Sadar, Panchari and Matiranga Upazilas of Khagrachari district, were surveyed. Data were collected, using a pre-tested questionnaire during January, 2015. The study revealed that turmeric farming is a profitable farming with some dominating variable costs like seed (rhizome) and sowing, harvesting and carrying. As the net return was Tk. 112139 per hectare and the BCR of sampled farmers was 2.20, this indicates that turmeric farms with a BCR greater than 1 have greater benefits than costs as well as positive net benefits. Seed (rhizome) and fertilizer showed significant positive effects on the turmeric production in the stochastic frontier production model. Turmeric farming displayed a mean technical efficiency of 82%, which suggested a substantial 18% of potential output of turmeric can be recovered by removing inefficiency. Besides improving technical efficiency, potential also exists for raising turmeric production through higher education and extension services. For a land scarce country like Bangladesh this gain could help increase income and ensure better livelihood for the hilly farmers. The policy implication of the analysis is that investment in education and extension service would greatly improve technical efficiency that contribute to income of the hilly people. Bangladesh J. Agril. Res. 44(1): 43-58, March 2019